The effect of the social aspect, media dependency, and uncertainty against the formation of Trust toward information in social network sites: A case study of COVID‐19 information in Indonesia. Issue 1 (5th July 2021) - Handarkho, Yonathan Dri; Widyastuti, Dhyah Ayu Retno; Harjoseputro, Yulius
Abstract: This study developed a comprehensive theoretical model to analyze individual Trust's formation concerning information related to COVID‐19 circulated in Social Network Sites (SNS) in Indonesia. The developed model used Social Impact, Uncertainty, and SNS Dependency theories. This study narrows the concept of Trust, which refers to how much individuals judge and consider the COVID‐19 information received in SNS as reliable and trustworthy. Data collected from 390 Indonesian respondents were used to analyze the proposed model via SEM analysis techniques. The findings indicated that SNS dependency had the most substantial immediate impact on Trust. Meanwhile, the result from a social impact perspective explicitly showed the various forms through which other people influence individuals' Trust in COVID‐19 information circulated in SNS. Uncertainty was also found to indirectly affect and moderate the direct impact of SNS dependency on Trust. However, this comprehensive observation has not been discussed thoroughly from a social perspective by prior studies and can contribute to future research. The indirect and moderating effects were additional contributions of this study that had not been profoundly utilized by previous related research.